The Effect of Reliability, Responsiveness and Tangible on Satisfaction and Loyalty of Tax Payer Earth Building (PBB) In The Department of Revenue, Finance and Asset Management Ngawi, Jawa Timur - Palupi, Galuh Dwianita (STIE AUB Surakarta)
This study aims to determine the effect Reliability, Responsiveness And Keberwujudan Satisfaction and Loyalty taxpayer Earth Building (PBB) at the Department of Revenue, Finance and Asset Management Ngawi. The technique of collecting data using questionnaires, the sample used taxpayer earth buildings in the Office of Revenue, Finance and Asset Management Ngawi totaling 100 respondents. The data analysis technique used is path analysis (path analysis), which will be tested by t test, F test and R2, Correlations, direct effect and the indirect effect and the total effect. From the T test results obtained that variable Reliability positive influence and no significant effect on satisfaction, Responsiveness positive influence and significant to satisfaction, Keberwujudan positive and significant impact on satisfaction, Reliability effect positive and significant impact on loyalty, Responsiveness positive effect and no significant effect on loyalty, Keberwujudan and significant positive effect on loyalty, satisfaction and significant positive effect on loyalty. The test results simultaneously (Test F) can be concluded jointly variable reliability, responsiveness and keberwujudan effect on performance. The test results showed that the coefficient of determination R2 total values are: = 0.787 or 78.7%. This means that performance, explained by the variable reliability, responsiveness and satisfaction keberwujudan by 78.7%. and the balance of 21.3% is explained by other variables outside the research model. Results of path analysis showed that the direct effect of reliability and loyalty keberwujudan greater than the indirect effect keberwujudan reliability and loyalty through customer satisfaction and responsiveness direct influence on loyalty through satisfaction is smaller than the direct effect of responsiveness to loyalty. Keywords: Reliability, Responsiveness, Keberwujudan, Loyalty, Satisfaction.